Universal Design for Learning-Based Inclusive Classroom Management at SD Labschool UNESA 2 Surabaya - Aliya Marsya As-syifa'; Hitta Alfi Muhimmah (Universitas Negeri Surabaya, 2026)
Inclusive education in Indonesia faces a persistent gap between normative policy commitments and actual classroom practice, particularly in how teachers manage heterogeneous classrooms at the primary school level. This study aims to describe inclusive classroom management based on Universal Design for Learning (UDL) at SD Labschool UNESA 2 Surabaya, focusing on: (1) physical and social environment management, (2) instructional differentiation and student grouping, and (3) facilitating and inhibiting factors of implementation. A descriptive qualitative approach was employed, with data collected through structured observation, semi-structured interviews with a class teacher and a special education companion teacher (GPK), and documentation on 6 May 2026. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), with triangulation and member checking to ensure credibility. Findings reveal that all three UDL principles multiple means of representation, engagement, and action and expression are implemented in an integrated manner through instructional differentiation, flexible assessment, peer tutoring, positive behavior management, and inclusive school culture. The school’s affiliation with Universitas Negeri Surabaya (UNESA) serves as a key institutional facilitator distinguishing it from regular inclusive schools. This research contributes empirical documentation of how UDL principles are operationalized in inclusive classroom management in the Indonesian primary school context.